Comprensión lectora y logro de competencias matemáticas en estudiantes de segundo grado de educación primaria en la I.E 60050 República de Venezuela de Iquitos 2022 - Encina Seopa, Johana Marfith (2023)
The aim of this study was to determine the relationship between reading comprehension and achievement of mathematical skills in students of the second grade of primary education at IE 60050 Republica de Venezuela de Iquitos in 2022. Materials and methods: It was applied a Reading comprehension diagnostic test to 101 students, previous validation for experts. The study was descriptive – relational and the design was not experimental and transversal. It was observed that there is a significant relationship between reading comprehension and mathematics learning (Tb=0,425) significance p = 0,00 < 0,05. Conclusion: The levels of reading comprehension determine the achievement of mathematical skills in students of the second grade of primary education are in the IE 60050 República de Venezuela of Iquitos